Exposure to West Nile virus and tick‐borne encephalitis virus in dogs in Spain. Issue 3 (11th January 2018) - García‐Bocanegra, I.; Jurado‐Tarifa, E.; Cano‐Terriza, D.; Martínez, R.; Pérez‐Marín, J. E.; Lecollinet, S.
Summary: In the past decade, the spread of emerging zoonotic flaviviruses (genus Flavivirus, family Flaviviridae ) has been reported in many regions worldwide, representing a threat to both human and animal health. A serosurvey was carried out to assess exposure and risk factors associated with antigenically related flaviviruses, particularly West Nile virus (WNV), Usutu virus (USUV) and tick‐borne encephalitis virus (TBEV), in dogs in Spain. Flavivirus antibodies were detected in 39 of 815 dogs (4.8%; 95% CI: 3.3–6.3) by bELISA. Significantly higher seropositivity was observed in hunting dogs compared to pet dogs. Virus neutralization tests confirmed WNV‐specific and TBEV‐specific antibodies in 11 and 14 bELISA‐positive dogs, respectively. This is the first serosurvey of WNV and TBEV in dogs in Spain and the first report of TBEV circulation in this country. The seropositivity obtained indicates widespread, but not homogeneous, distribution of WNV and TBEV in dogs in Spain. In 2013 and 2015, WNV‐seropositive dogs were detected in those areas of Andalusia where the highest number of WNV outbreaks were reported in both horses and humans. Antibodies against TBEV have been found in dogs sampled in two different periods and regions in Spain. Serosurveillance in dogs could be a complementary way of monitoring the activity of emerging flaviviruses in Spain.